Osculating hypersurfaces of higher order - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2011)
Oscurating surfaces of second order have been studied in classical differential geometry [1]. In this article we generalize this notion to osculating hyper-surfaces of higher order of hyper-surfaces inEuclidean n-space. Various related results are obtained using the derivatives of higher order.
Keywords: hypersurface; osculating hypersurface